Analysis of Heavy Metal Cadmium in Aquatic Plants in the Brantas River, Mojokerto City - Najihah, Nailin; Rachmadiarti, Fida (LenteraBio : Berkala Ilmiah Biologi, 2023)
Brantas is a river that plays an important role for people of East Java. Throughout the watershed several industries that produce heavy metal Cd and these activities involved decreasing the quality of river water. This study aims to determine Cd of aquatic plants and river water in Brantas Mojokerto, determine the relationship Cd in water and plants, determine the condition river waters in terms of physical and chemical factors. The research conducted from September 2022 to January 2023. Sampling carried out at 3 stations on Jl.Hayam Wuruk and Jl.Major Sungkono Mojokerto. Each station taken 2 points, at each point, 3 type plants taken, namely kale(Ipomea aquatica), water hyacinth(Eichhornia crassipes), genjer(Limnocharis flava). Testing cadmium carried out at Airlangga University using Atomic Absorption Spectrophotometer(AAS) method. Data analysis carried out by comparing the results with quality standards, for water according to PP RI No.22 Th.2021 and aquatic plants to SNI:7387 Th.2009. The results showed the highest levels Cd found in kale at station I of 0.235+0.01 ppm, the highest levels Cd in water were 0.133+0.004 ppm at station I. These levels exceeded the quality standard of 0.2 ppm for plants and 0,01 ppm for water. All water quality tests met quality standards except turbidity.